Unveiling the Link Between Islamic Governance Practices and CSR Disclosure in Islamic Financial Institutions - Fakhruddin, Iwan; Amany, Ashilla Nadiya; Winarni, Dwi; Kusbandiyah, Ani; Pandansari, Tiara (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2025)
This research aims to determine the impact of Islamic Corporate Social Responsibility disclosure by considering the proportion of audit quality, number of SSB meetings, and level of implementation of Islamic Corporate Governance. The population in this research is Sharia Banking registered with the Financial Services Authority in 2018-2022. Using a purposive sampling approach, the sample includes all items required in each variable. Then, an analysis and hypothesis testing approach was carried out using panel data regression analysis using Stata 17. The results of audit quality testing obtained a significance value of 0.02, and the test of Islamic Corporate Governance was 0.736. This shows that the audit quality and Islamic Corporate Governance variables do not affect Islamic Social Reporting. However, the research results on the variables of Sharia supervisory board meetings have a significance value of 0.104 and a positive coefficient value. This shows that Sharia supervisory board meetings positively influence Islamic corporate governance. Stakeholders have basic desires and implement accountability mechanisms to ensure good monitoring, audit quality and reporting to help achieve organizational goals. However, self-introduction with the organization cannot prove commitment to better Sharia principles. This research also provides insight into indicators that need to be applied to Sharia banking and by Islamic principles in Sharia banking management.